Diabetes severity and the role of leisure time physical exercise on cardiovascular mortality: the Nord-Trøndelag Health study (HUNT), Norway - Moe, Børge (BioMed Central, 2013)
BACKGROUND: Physical activity has been associated with lower cardiovascular mortality in people with diabetes, but how diabetes severity influence this association has not been extensively studied. METHODS: We prospectively examined the joint association of diabetes severity, measured as medical treatment status and disease duration, and physical exercise with cardiovascular mortality. A total of 56,170 people were followed up for 24 years through the Norwegian Cause of Death Registry. Cox proportional adjusted hazard ratios (HRs) with 95% confidence intervals (CI) were estimated. RESULTS: Overall, 7,723 people died from cardiovascular disease during the follow-up. Compared to the reference group of inactive people without diabetes, people with diabetes who reported no medical treatment had a hazard ratio (HR) of 1.65 (95% CI: 1.34, 2.03) if they were inactive and a HR of 0.99 (95% CI: 0.68, 1.45) if they reported ≥2.0 hours physical exercise per week. Among people who received oral hypoglycemic drugs or insulin, the corresponding comparison gave HRs of 2.46 (95% CI: 2.08-2.92) and 1.58 (95% CI: 1.21, 2.05), respectively. CONCLUSIONS: The data suggest a more favourable effect of exercise in people with diabetes who used medication than in those who did not, suggesting that physical exercise should be encouraged as a therapeutic measure additional to medical treatment.